The properties of LaSrMnO3 powders synthesized at various regimes; Physica B: Condensed Matter; Vol. 521 - Mikhaylov M. M. Mikhail Mikhaylovich; Sokolovsky A. N. Aleksey Nikolaevich; Vlasov V. A. Vitaliy Anatolievich; Smolin A. E. Anton Evgenjevich (2017, 2017)
Title screen